Investigating associations of childhood abuse and serum brain-derived neurotrophic factor levels with suicidal behaviours in patients with depressive disorders - Kim, Jae-Min; Kim, Ju-Wan; Kang, Hee-Ju; Lee, Ju-Yeon; Kim, Sung-Wan; Shin, Il-Seon; Chun, Byung-Jo; Stewart, Robert (British journal of psychiatry, 2021)
The role of childhood abuse and serum brain-derived neurotrophic factor (BDNF) levels in suicidal behaviour is controversial. We aimed to investigate the individual and interactive effects of the childhood abuse and serum BDNF on suicidal behaviour before and after pharmacologic treatment in patients with depressive disorders. At baseline, reported childhood emotional, physical and sexual abuse were ascertained and serum BDNF levels were measured in 1094 patients with depressive disorder, 884 of whom were followed during a 1-year period of stepwise pharmacotherapy. Suicidal behaviours evaluated at baseline were previous suicide attempt and baseline suicide severity, and suicidal behaviours evaluated at follow-up were increased suicide severity and fatal/non-fatal suicide attempt. Individual and interactive associations of any childhood abuse and serum BDNF levels with four types of suicidal behaviours were analysed using logistic regression models, after adjusting relevant covariates. Individual associations of childhood abuse were significant only with previous suicide attempt, and no significant individual associations were found for serum BDNF with any suicide outcome. However, the presence of both childhood abuse and lower serum BDNF levels was associated with the highest prevalence/incidence of all four suicidal behaviours, with significant interactions for baseline suicide severity and fatal/non-fatal suicide attempt during follow-up. Synergistic interactive effects of child abuse and serum BDNF levels on suicidal behaviours were found before and after pharmacologic treatment in patients with depressive disorders. Information combining childhood abuse and serum BDNF levels could improve predictions of suicidal behaviour in patients with depressive disorders.